INFLUENCE OF FILLER, MONOMER MATRIX AND SILANE COATING ON COMPOSITE RESIN ADHESION - PĂSTRAV, Mihaela; MOLDOVAN, Marioara; CHISNOIU, Andrea; SAROȘI, Codruța; MIUȚA, Filip; PĂSTRAV, Ovidiu; DELEAN, Ada; CHISNOIU, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2021)
This study compared marginal microleakage in case of two dental composite resins: a consecrated commercial Bis- GMA resin- IPS Empress Direct (Ivoclar Vivadent, Lichtenstein)- group A, and a recently introduced Bis- MEPP resin - Gaenial A’Chord (GC R&D Japan)- group B and to observe, by means of scanning electron microscopy (SEM), the differences between these two restorative materials when using the same adhesive system and restorative layering technique. Microleakage testing scores were higher in IPS Empress group, but the results were not statistically validated. SEM images on group A presented a highly developed hybrid layer, while for group B resin extension intersecting the hybrid layer were observed, having a similar electronic density with the adhesive layer, which demonstrates a continuity of the nanoparticles in depth. On dentin- composite interface increased number of gaps and fissures were observed, comparing to enamel-composite interface. The result from the research showed that the two compared composite resin present similar properties in terms of adhesion and microleakage.